Dysfunction of pulmonary epithelial tight junction induced by silicon dioxide nanoparticles via the ROS/ERK pathway and protein degradation. (September 2020) - Liu, Yingqi; Wei, Haiyan; Tang, Jing; Yuan, Jiaming; Wu, Mingmin; Yao, Chenjuan; Hosoi, Kazuo; Yu, Shali; Zhao, Xinyuan; Han, Yu; Chen, Gang
Abstract: Silica nanoparticles (SiNPs) are one of the most widely used types of nanoparticles across many industrial sectors, and are known to be present in the air year-round. In this study, we aimed to evaluate the potential adverse effects of SiNP exposure on pulmonary epithelial tight junctions, which serve as a critical barrier between the respiratory system and the circulatory system. In vivo studies confirmed that SiNPs decreased the protein expression levels of zonula occludens 1 (ZO-1), zonula occludens 2 (ZO-2), and occludin in the lungs of C57BL/6 mice. In vitro studies showed that SiNPs not only decreased the mRNA and protein expression of ZO-1 and ZO-2, but also decreased the protein expression of occludin in human bronchial epithelial (BEAS-2B) cells. In addition, SiNP exposure increased reactive oxygen species (ROS) production and activated extracellular regulated protein kinases (ERKs) and c-Jun N-terminal kinase (JNK). The inhibition of ROS and ERKs effectively protected the SiNP-induced downregulation of ZO-1 mRNA and protein expression, but had no effect on ZO-2 or occludin expression. SiNP-induced matrix metalloproteinase 9 (MMP9) protein expression appeared to be involved in occludin proteolytic degradation, in addition to SiNP-induced direct occludin protein degradation. The present study suggests that SiNPs disturb pulmonary epithelial tight junction structure and function via the ROS/ERK pathway and protein degradation. Graphical abstract: Image 1 Highlights: The study firstly tested the effect of SiNPs on pulmonary epithelial tight junctions. SiNPs significantly decreased tight junction proteins ZO-1, ZO-2, and occludin. SiNP-induced reduction in ZO-1 is ROS-dependent through activation of ERK. SiNPs enhanced occludin protein degradation.